Meningkatkan Kemampuan Berbicara Anak Usia Dini melalui Media Kartu Bergambar pada Kelompok A di Paud Mawar Kecamatan Bunga Dani - Sri Bintang Rejeki (ALAYYA : Jurnal Pendidikan Islam Anak Usia Dini, 2021)
Astract This research is a type of classroom action research conducted collaoratively etween teachers and researchers. This study aims to improve the speaking aility of early childhood group A through the singing method with audiovisual media for PAUD Mawar Bungo Dani District. The root of the prolem in this writing is how the singing method with audiovisual media can improve language skills in children. The writing of this class action was carried out in 2 cycles with 16 children consisting of various parental ackgrounds. Childrens data is taken ased on oservations learning outcomes data and question scripts or instruments. Data analysis used a percentage technique which was made per cycle. The results of the study starting at the Precycle Cycle I and Cycle II stages showed that there was an increase in the childs aility in language skills. The achievement of the precycle language skills efore the action was 15.39% the first cycle was 61.53% and the second cycle was 84.61%.